FUNGSI JIWA CAMPURAN: BERBAGAI BENTUK GEJALA JIWA MANUSIA DAN APLIKASINYA DALAM DUNIA PENDIDIKAN - Inarotul Chasanah; Halimatus Sa’diyah; Faiqotul Hikmah; Titin Nurhidayati (As-Sulthan Journal of Education, 2026)
This study aims to examine the relationship between the symptoms of a mixed soul, namely the integration of the functions of reason ('aql), heart (qalb), and desire (nafs), and the formation of student character within the framework of Islamic Educational Psychology. The study was conducted using a qualitative-descriptive approach through library research, examining Islamic literature, contemporary educational psychology, and character education in Islamic educational institutions. The findings indicate that when these elements of the soul are out of balance, for example, when reason fails to control desires, or the heart fails to act as a moral guide, symptoms of a mixed soul emerge, including unstable motivation, inner conflict, and immature character behavior. Conversely, Islamic religious education, which consciously instills spiritual, emotional, and moral values, and effectively integrates the functions of reason, heart, and desire, contributes positively to the strengthening of student character. As psychological beings, humans possess complex and interacting mental functions. In psychological studies, mental functions generally encompass cognitive, affective, and conative aspects. These three functions do not operate in isolation but often appear in a mixed form, influencing an individual's behavior, emotions, and learning process. This article aims to examine the concept of mixed mental functions, the various forms of human mental symptoms that arise from the interaction of these functions, and their application in education. The method used is a literature review of psychological and educational theories. The results of this study indicate that understanding mixed mental functions is crucial for educators in designing holistic, humanistic learning strategies that are oriented towards the overall development of students.